Primary Teachers’ Perceptions of Mindfulness Practices With Young Children (LEARNing Landscapes, 2017)
Recent research into mindfulness in education supports introduction of this practice into the classroom. This qualitative descriptive study explored mindfulness with young children, as perceived by their teachers. Four primary teachers were interviewed using open-ended and semi-structured questions, allowing them to share their experiences of implementing mindfulness in their classrooms. Using thematic analysis, we learned that teachers found benefits of including mindfulness into daily classroom routines. However, they felt that more holistic approaches, such as guided breathing, yoga, and lovingkindness meditation, could more fully support childhood well-being.
Keywords: well-being; mindfulness; young children; interview; thematic analysis